Palladacycles for directed and nondirected C H bond functionalization of (Hetero)arenes - Soni, Vineeta; Punji, Benudhar (Strategies for palladium-catalyzed non-directed and directed C-H bond functionalization, 2017)
Application of palladacycle complexes in catalytic organic transformation is rapidly expanding. This chapter is mainly focused on the use of palladacycle precatalysts in CH bond functionalizations, as well as an overview of palladacycle intermediates in directed CH bond functionalization reactions. The described palladacycle precatalysts are more efficient and more selective than the traditional palladium complexes for CH bond functionalization processes. The second part of the chapter summarizes the involvement of palladacycle intermediates in various directed CH bond functionalizations that are proposed with experimental evidence. Some of the palladacycle intermediates described are shown to be competent as catalyst precursors. It has been demonstrated that the formation of palladacycle (precatalyst or intermediate) makes the CH functionalization process more facile, because of the high stability associated with palladacycles.

Pd(II)-catalyzed chemoselective acetoxylation of C(sp(2))-H and C(sp(3))-H bonds in tertiary amides - Vijaykumar, Muniyappa; Punji, Benudhar (Journal of Organic Chemistry, 2021)
Palladium-catalyzed chemoselective C(sp(2))-H and C(sp(3))-H acetoxylation of synthetically useful tertiary amides is reported under relatively mild reaction conditions. This protocol proceeds through the assistance of a weakly coordinated directing group (C = O) and requires low catalyst (1.0 mol %) loading. Diverse functionalities, such as C(sp(2))-Cl, C(sp(3))-Cl, -CF3, -COOEt, and -NO2 groups, including morpholinyl, piperazinyl, and pyrrolidinyl heterocycles, are compatible under the reaction conditions. Further functionalization of this protocol is demonstrated by hydrolysis to alcohols, alcohol-acids, as well as reduction to tertiary amines. A preliminary kinetic isotope effect study supported the rate-limiting C-H bond activation process.

Palladium-catalyzed chemoselective oxygenation of C(sp2)-H and C(sp3)-H bonds in isatins - Vijaykumar, Muniyappa; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Organic Letters, 2023)
The palladium-catalyzed chemoselective C(sp2)-H and C(sp3)-H bond oxygenation of substituted isatin derivatives is reported. This mild protocol exhibits the C5 C(sp2)-H oxygenation of isatins through electrophilic intermolecular C-H palladation in concentrated solutions using PhI(OAc)2 or Selectfluor as an oxidant, whereas it exhibits- N-CH3 C(sp3)-H oxygenation in dilute solutions via carbonyl-assisted intramolecular palladation in the presence of K2S2O8. This oxygenation reaction provides a direct and unified approach for synthesizing diverse oxygenated isatins with sensitive functionalities, including biorelevant compounds.

Palladium-catalyzed regioselective C(4)-H fluoroalkoxylation of indoles through weak chelation assistance - Vijaykumar, Muniyappa; Gonnade, Rajesh G.; Punji, Benudhar (ChemCatChem, 2025)
Installing fluoroalkyl motifs into biorelevant indoles is particularly interesting due to their ubiquitous presence in drug molecules. Herein, we demonstrate the regioselective C4 fluoroalkoxylation of indoles using fluoroalcohols via palladium-catalyzed chelation-assisted C & horbar;H activation. The weak chelating benzoyl moiety at the C3 position acts as a directing group for remote C(4)& horbar;H fluoroalkoxylation of diversely substituted indoles. This methodology demonstrates a high level of regioselectivity and tolerates a range of crucial functional groups, yielding diverse trifluoroalkoxylated indoles in moderate to good yields. Removal of directing/protecting groups and further functionalization established the synthetic utility of the methodology. A preliminary mechanistic investigation is conducted by isolating the palladacycle intermediate and performing the deuterium scrambling study. The regioselective C4 fluoroalkoxylation of indoles with various fluoroalcohols is achieved by the palladium-catalyzed weak chelation assistance strategy. The reaction is compatible for a range of important functionalities and proceeds via the intermediacy of a six-membered palladacycle following a Pd(II)/Pd(IV) pathway. image
Keywords: C-H activation; indoles; Palladium; Regioselective; Trifluoroalkoxylation